Thomas Quaife "Media credibility as perceived by central Iowa farmers" ; Adi Widjono "Perception of Superiors' Openness to Upward Information In an Indonesian Food Crops Agricultural Development Organization" - Cliff Scherer; Donald Schwartz (Journal of Applied Communications, 1986)
Reports on unpublished theses.